Steeping Bay Leaves (Syzygium Polyanthum) to Increase Cholinesterase Levels Due to Pesticide Exposure in Farmers - Sujarwadi, Mokh.; Toha, Mukhammad; Zuhroidah, Ida (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Farmers are at high risk of pesticide exposure. The threat of death from pesticides reaches 168,000 per year. Pesticide free radicals cause health problems in the form of impaired function of nerves, liver, and kidneys and cause cancer. Low blood cholinesterase (CHE) indicates pesticide residue. Steeping bay leaves (Syzygium polyanthum) are expected to improve liver function to detoxify pesticide-free radicals that have already entered the body. This study aims to determine the effect of steeping bay leaves (Syzygium polyanthum) on increased cholinesterase (CHE) levels. Qualitative research with pre-experimental design one group pre-test-post test. As a population is a group of farmers in the Pasuruan area. The sample size in this study was 20 respondents using purposive sampling techniques. The research procedure is to measure cholinesterase levels in the blood before and after steeping bay leaves (Syzygium polyanthum) after 15 days. The data were analyzed by paired t-test. There was an increase in average blood cholinesterase levels of 399.35 U/L after 15 days of regular consumption. Blood cholinesterase levels before treatment were 5,301.25 U/L and after treatment became 5,700.00 U/L. The paired t-test results showed a significance value of p = 0.000. The average working time of the participants 18.5 years is very likely to have a lot of pesticide residues in their bodies and cause disruption of the normal function of several organs, causing mild and severe health problems. Bay leaf steeping (syzygium polyanthum)has been shown to increase cholinesterase (CHE) levels. To avoid the threat of health problems, farmers should diligently consume steeping bay leaves regularly.